1976
DOI: 10.1259/0007-1285-49-587-903
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of pneumographic cerebellar atrophy

Abstract: The clinical significance of apparent pneumographic cerebellar atrophy has been studied in a group of 44 otherwise unselected patients found to have cerebellar atrophy, according to previously suggested criteria, at pneumoencephalography. Lateral and postero-anterior tomography of the posterior fossa was performed in all these cases. In each case the width of two or more sulci in the cerebellar vermis exceeded 2 mm. We have concluded that: (1) There is a relationship between the severity of pneumographic cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Neuropathological studies report that about one quarter of autopsied cases of alcohol dependence show evidence of cerebellar pathology (Phillips et al, 1987; Torvik et al, 1982). It is also known from early pneumoencephalographic and more recent CT and MRI studies that cerebellar tissue loss may appear in a significant number of alcohol-dependent subjects (Carlen et al, 1986; Haubek & Lee, 1979; Hillbom, Muuronen, Holme, & Hindmarsh, 1986; Kennedy, Swash, & Wylie, 1976). These neuropathologic and radiologic studies also showed that cerebellar atrophy, or tissue volume loss, or both may be observed in the absence of clinical signs such as ataxia or obvious cognitive impairment.…”
mentioning
confidence: 99%
“…Neuropathological studies report that about one quarter of autopsied cases of alcohol dependence show evidence of cerebellar pathology (Phillips et al, 1987; Torvik et al, 1982). It is also known from early pneumoencephalographic and more recent CT and MRI studies that cerebellar tissue loss may appear in a significant number of alcohol-dependent subjects (Carlen et al, 1986; Haubek & Lee, 1979; Hillbom, Muuronen, Holme, & Hindmarsh, 1986; Kennedy, Swash, & Wylie, 1976). These neuropathologic and radiologic studies also showed that cerebellar atrophy, or tissue volume loss, or both may be observed in the absence of clinical signs such as ataxia or obvious cognitive impairment.…”
mentioning
confidence: 99%